NATURE OF INTELLECTUAL PROPERTY INSURANCE AND ITS ROLE IN MODERN ECONOMY - V. Bazylevych; V. Virchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Article is devoted to theoretical analysis of nature and mechanism of intellectual property insurance. Types of intellectual property relations and its role in public reproduction are investigated. Peculiarities of intellectual property relations are considered. Classification of intellectual property objects depending on their most essential features is analyzed. Different approaches to classification of intellectual property subjects are considered. Nature and preconditions of origin of intellectual property insurance are investigated. Goals and functions of intellectual property insurance are specified. Risks that related to disposal and commercialisation of intellectual property and connected with peculiarities of intellectual property objects and growing rate of intellectual property rights infringements are analyzed. Three groups of risks concerning disposal and commercialization of intellectual property objects are singled out: risks related to loss or abridgement of intellectual property rights; risks related to possible losses, contingencies and half-received profits connected with commercialization of intellectual property objects; risks of professional responsibility of participants of intellectual property market. On the basis of analysis of hands-on experience four types of intellectual property insurance are investigated: insurance of intellectual property rights; liability insurance of the intellectual property subjects; professional liability insurance of participants of intellectual property market; liability insurance of the contractors concerning intellectual property disposal. Factors that restrains development of intellectual property insurance in Ukraine are analyzed.